Pelatihan Microlearning Berbasis Gamification dengan Wordwall Bagi Guru SMP IT Ibnu Sina - Tutik Yuliatun; Aprilita Ekasari; Susanti, Susanti; Khusnatul Amaliah (Yayasan Literasi Sains Indonesia, 2024)
Technological developments are taking place increasingly rapidly, thereby changing the order of life in various aspects. This can also be seen from one of the government's efforts to integrate the independent campus independent learning program which has the aim of bringing students to become competent learners in the 21st century. Therefore, Community Service activities are carried out which have the aim of equipping Ibnu Sina IT Middle School Teachers. in applying ICT to learning. The ICT applied in learning is in the form of gamification-based microlearning with word walls. The method used in this activity is training and was carried out from August to September 2023. This training was carried out in 5 activity stages including: (1) observation, analysis of the situation and conditions of partners; (2) planning, in the form of providing solutions to problems faced by partners and preparing activity guide modules; (3) socialization of activity plans, distribution of activity guide modules, and things that need to be prepared in implementing training; (4) training and mentoring, namely the implementation of training in the form of an overview of microlearning, gamification and wordwall, which is then provided with mentoring in the wordwall; (5) monitoring and evaluation, in the form of usefulness of training, effectiveness and efficiency in implementation. Based on all stages of activity, the results are that teachers are able to use and implement gamification-based microlearning with wordwalls in learning.